PENDIDIKAN SEBAGAI ALAT TRANSFOMASI SOSIAL - Asryani; Gisca; Santi; Maulfira Magda Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this study is to examine the role of the Dutch Ethical Policy in shaping national consciousness and the emergence of an indigenous intellectual elite who became agents of change in the struggle for Indonesian independence. The research employs a qualitative method with a historical approach, analyzing historical documents, colonial archives, and relevant literature. The findings reveal that although the Ethical Policy was intended to serve colonial interests, it inadvertently provided opportunities for education and increased social awareness among the indigenous elite. These individuals became key drivers of social transformation, fostering resistance against colonial rule and advocating for independence through organizations, education, and the media. This study concludes that colonial education served as a crucial instrument for social change and the development of Indonesian nationalism, with the indigenous intellectual elite playing a central role in the independence movement.